Some Important Observations on the Populations of Hooded Vultures Necrosyrtes monachus in Urban Ghana - Gbogbo, Francis; Roberts, Japheth S. T.; Awotwe-Pratt, Vincent (International Journal of Zoology, 2016)
Despite major declines in the population of vultures around the world, noticeable increases were reported in the populations of Hooded Vultures Necrosyrtes monachus over the past decade in Accra—an important vulture habitat in Ghana. In recent times, however, there is a growing concern that the vulture numbers are decreasing even though scientific data to support this is nonexisting. As a vital zoogeographical and conservation tool, it is important to keep an up-to-date knowledge about urban bird populations amidst rapid urbanization and associated changes. Using a combination of field data, literature review, and stakeholder consultations, it was indicative that severe decline might have indeed occurred in the populations of Hooded Vultures in Accra. Evidence suggests the killing of vultures for consumption, traditional medicine, and black magic in an undercover trade with possible transboundary connections as important underlying factor. Additional factors suspected to underlie the declines include changes in management of urban facilities and destruction of roosting and nesting trees. The implications of interspecific competition with Pied Crows Corvus albus on Hooded Vultures however remain unclear. There is an urgent need for conservation campaign and education to save the Hooded Vulture in Ghana.